Treatment of Uterine Myoma with 2.5 or 5 mg Mifepristone Daily during 3 Months with 9 Months Posttreatment Followup: Randomized Clinical Trial. (29th July 2013) - Carbonell, Josep Lluis; Acosta, Rita; Pérez, Yasmirian; Garcés, Roberto; Sánchez, Carlos; Tomasi, Giuseppe
Abstract : Objectives . To evaluate the efficacy, safety, and quality of life by using 2.5 and mifepristone 5 mg daily doses to treat uterine fibroids over 3 months with a 9-month followup period. Design . Randomized clinical trial. Place . "Eusebio Hernández" Hospital, Havana, Cuba. Subjects . 220 women with symptomatic uterine fibroids. Treatment . One-half (2.5 mg) or one-whole 5 mg mifepristone tablet. Variables to Evaluate Efficacy . Changes in fibroid and uterine volumes, in symptomatic prevalence and intensity, and in quality of life. Results . After 3-month treatment, fibroid volume decreased by 27.9% (CI 95% 20–35) and 45.5% (CI 95% 37–62), in the 2.5 and 5 mg groups, respectively, P = 0.003 . There was no difference in the prevalence of symptoms at the end of treatment, unlike after 6- and 9-month followup when there was a difference. Amenorrhea was significantly higher in the 5 mg group, P = 0.001 . There were no significant differences in mifepristone side effects between the groups. Both groups displayed a similar improvement in quality of life. Conclusions . The 2.5 mg dosage resulted in a lesser reduction in fibroid size but a similar improvement in quality of life when compared to the 5 mg dose. This trial is registered with ClinicalTrials.gov NCT01786226 .